Economic Value Added, dan Market Value Added Sebagai UkuranKinerja Keuangan Perusahaan (Studi Pada Perusahaan LQ45 Yang Terdaftar di BEI Periode 2016- 2018) - Dimas Respati Argeswara (Jurnal Ilmiah Mahasiswa FEB, 2019)
aximizing company’s wealth and its shareholders is the main objective for acompany. Several measurement tools to determine company’s financial performance areEconomic Value Added (EVA) and Market Value Added (MVA). Financial performance canrepresent the rate of return of wealth that has been generated for investors and the companyitself. This research has the objective to find out the result of companies’ financialperformance with Economic Value Added and Market Value Added on LQ45 companieslisted on the Indonesian Stock Exchange.This type of research is quantitative descriptive which means a research thatconducted to find out the value of independent variable, either it has one variable or more(independent) without making any comparison, or connecting any other variables. Samplesthat this research used are LQ45 companies listed on the Indonesian Stock Exchange for theperiod of 2016-2018.The results are companies listed on LQ45 have positive Economic Value Added andMarket Value Added values, so that companies listed on LQ45 are in good condition andcompanies have increased their wealth also its investors as well.Keywords: Financial Performance, Economic Value Added (EVA) and Market Value Added(MVA)